Analisis kemampuan guru dalam penggunaan perangkat chromebook pada pembelajaran IPAS di kelas V sekolah dasar - Eska Asanti; Siti Istiyati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2024)
The aim of this research is to describe teachers' abilities in using chromebook media in science and social studies learning in class V of SD Negeri Cinderejo, Surakarta city. This research is qualitative descriptive research with a case study approach. The research subject was a fifth grade teacher at Cinderejo State Elementary School, Surakarta City. The data collection techniques used were written tests, observations, interviews. and documentation. Content validity is carried out by expert assessment. Data validity uses source triangulation and technical triangulation. The data analysis used is the interactive analysis of the Miles and Huberman model. The research results show that the ability of class V teachers to use chromebook media is theoretically in the "very good" category with an average score for each variable of 90.75% obtained through test results. However, the practical ability of class V teachers in using chromebook media in science and science learning in class V is included in the "sufficient" category with a score of 41.9% obtained through observation results. Based on the research results, it can be concluded that the teacher's teachers' abilities in using chromebook media in science and social studies learning in class V of SD Negeri Cinderejo, Surakarta City has a gap between theory and practice due to time factors and technical support.